Can the gains from Argentina's utilities reform offset credit shocks? - Daniel A. Benitez; Omar O. Chisari; Antonio Estache (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Relying on a general equilibrium model of Argentina's economy calibrated for 1993 and internalizing all productivity and scale gains achieved up to 1999, this paper isolates the distributional effects of utilities reform from the impact of other reforms taking place in the country during the 1990s. The analysis shows that both private and public agents gain from the increases in productivity and in service access made possible by the utilities reform. In the short term, the public sector benefits from the proceeds of the sale of firms and the associated debt reduction, but greater advantages in the long term accumulate from the expanded taxbase and from the reduction in expenditure flows. Private agents gain from lower costs, lower average tariffs, and improvements in service quality as well as greater employment opportunities resulting from lower production costs. These welfare gains, however, are substantially offset by the `tequila' and `vodka' shocks that hit the country during the 1990s and increased rationing in the credit markets. The distributional effects of the utilities reform are generally positive at this macroeconomic level of analysis, but this often implies a strong commitment to an effective regulatory regime to prevent capture of the contributions of reform by the capital owners of the utilities sector.
Keywords: C68; L5; 330; computable general equilibrium; regulation; Allgemeines Gleichgewicht; Versorgungswirtschaft; Regulierung; Privatisierung; Argentinien